Impacts of vitamin premix and/or yeast ingredient inclusion in a canned cat food on thiamin retention during 6 months of storage - Dainton, Amanda N.; White, Brittany; Lambrakis, Leah; Aldrich, Charles Gregory (Frontiers in Veterinary Science, 2022)
Low thiamin levels in thermally processed canned cat foods are concerning for the pet food industry. However, there is little information on storage stability of thiamin in this food format or if inclusion of select ingredients, such as dried yeasts, has an effect. Therefore, the objective was to evaluate the storage stability of thiamin when a vitamin premix and/or yeasts ingredients were included in a canned cat food. The factorial treatment arrangement consisted of 2 levels of vitamin premix (with or without) and 4 inclusions of yeast (NY = none, LBV = Lalmin B Complex Vitamins, BY = product #1064B, or EA = BGYADVANTAGE). Diets were stored for 6 months and analyzed every month for thiamin. Data were analyzed as a mixed model (SAS v. 9.4; SAS Institute, Cary, NC) with fixed effects (vitamin premix, yeast, time, and their two-way and three-way interactions) and random effects (production day and the interaction of production day, vitamin premix, and yeast). Significance was set at P < 0.05 and Fisher’s LSD was used to separate means. Diets including the vitamin premix [average 55.1 mg/kg dry matter basis (DMB)] contained more (P < 0.05) thiamin than diets that did not (average 7.5 mg/kg DMB). Inclusion of LBV (average 40.3 mg/kg DMB) resulted in the highest (P < 0.05) levels of thiamin, followed by BY (P < 0.05; average 26.9 mg/kg DMB). Diets with NY and EA contained the lowest (P < 0.05) levels of thiamin and were not different from each other (P > 0.05; average 19.3 mg/kg DMB). The diet containing vitamin premix without yeast lost (P < 0.05) 17.8% thiamin while diets containing a yeast ingredient maintained thiamin levels better during storage. This suggested that thiamin from yeast ingredients was more resistant to degradation during storage and should be considered when designing new canned cat foods.